Toll-like receptor 2 -196 to -174 del polymorphism influences the susceptibility of Han Chinese people to Alzheimer's disease - Yu, Jin-Tai (BioMed Central, 2011)
BACKGROUND: Toll-like receptor 2 (TLR2) represents a reasonable functional and positional candidate gene for Alzheimer's disease (AD) as it is located under the linkage region of AD on chromosome 4q, and functionally is involved in the microglia-mediated inflammatory response and amyloid-β clearance. The -196 to -174 del polymorphism affects the TLR2 gene and alters its promoter activity. METHODS: We recruited 800 unrelated Northern Han Chinese individuals comprising 400 late-onset AD (LOAD) patients and 400 healthy controls matched for gender and age. The -196 to -174 del polymorphism in the TLR2 gene was genotyped using the polymerase chain reaction (PCR) method. RESULTS: There were significant differences in genotype (P = 0.026) and allele (P = 0.009) frequencies of the -196 to -174 del polymorphism between LOAD patients and controls. The del allele was associated with an increased risk of LOAD (OR = 1.31, 95% CI = 1.07-1.60, Power = 84.9%). When these data were stratified by apolipoprotein E (ApoE) ε4 status, the observed association was confined to ApoE ε4 non-carriers. Logistic regression analysis suggested an association of LOAD with the polymorphism in a recessive model (OR = 1.64, 95% CI = 1.13-2.39, Bonferroni corrected P = 0.03). CONCLUSIONS: Our data suggest that the -196 to -174 del/del genotype of TLR2 may increase risk of LOAD in a Northern Han Chinese population.